(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
The hydroxycarboxylic acid family of receptors (ENSFM00500000271913, nomenclature as agreed by the NC-IUPHAR Subcommittee on Hydroxycarboxylic acid receptors [32, 10]) respond to organic acids, including the endogenous hydroxy carboxylic acids 3-hydroxy butyric acid and L-lactic acid, as well as the lipid lowering agents nicotinic acid (niacin), acipimox and acifran [47, 54, 57]. These receptors were provisionally described as nicotinic acid receptors, although nicotinic acid shows submicromolar potency at HCA2 receptors only and is unlikely to be the natural ligand [54, 57].